Synovia modrej planéty (Syny goluboj planety) - Lebedev, L.; Lukjanov, B.; Romanov, A.; Capiak, Alojz (Bratislava Pravda, 1974)
Kniha zachytáva prvé desaťročie úspechov sovietskej kozmonautiky.
Keywords: kozmonautika; dejiny kozmonautiky; kozmonauti sovietski; astronómia; astrofyzika; rozprávanie; prírodné vedy; ZSSR; ZSSR